ANALISIS PRINSIP KEADILAN TENTANG SYARAT MENJADI ANGGOTA LEGISLATIF BAGI KEPALA DESA BERDASARKAN UNDANG – UNDANG NOMOR 7 TAHUN 2017 DAN PERATURAN KOMISI PEMILIHAN UMUM NOMOR 20 TAHUN 2018 - Muhammad Sayuni; Elidar Sari; Sulaiman Sulaiman (Program Studi Magister Hukum Universitas Malikussaleh, 2021)
General Election is a means of implementing people's sovereignty which is carried out directly, freely, secretly, honestly and fairly based on the Pancasila and the 1945 Constitution of the Republic of Indonesia. Implementation of Elections is the implementation of the stages of elections which are carried out freely, fairly, and honestly. The purpose of this study is to analyze the principle of justice in the requirements to become a legislative member for the Village Head based on Law Number 7 of 2017 and Election Commission Regulation Number 20 of 2018. The results of the study showed that the first election held in 2019 did not implement the principles of justice in terms of the legislative candidate for the Village Head. The public can provide legal certainty for the implementation of the 2019 Election law. It is recommended to the General Election Commission to revise the Election Commission Regulation regarding the nomination of members of the DPR, Provincial DPRD, and Regency / City DPRD specifically in the requirements for candidates for the Village Head in Article 8 paragraph 1 letter b number 6 point b, to guarantee the rights of citizens and fulfill the principles of justice.